(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2011)
Constitutional Amendment 45, of December 8, 2004, added the principle of a reasonable length of proceedings to the list of individual and collective rights and duties (item XXVIII of article 5 of the Federal Constitution). This study aims to address the applicability of this principle to tax enforcement proceedings. As the national legal community knows, the processes governed by Law No. 6.830/80 (Tax Enforcement Law - LEF) and, subsidiarily, by the Code of Civil Procedure, on the one hand are marked by the typical simplification of enforcement proceedings. On the other hand, it is characterized by eternalization. In fact, it is not difficult to find cases filed many decades ago (50 or 60 years ago, for example), either in the courts or in the archives of overdue cases in the Judiciary. In October 2011, the Federal Judicial Sub-section of São Paulo alone had 240,462 cases, while the backlog totaled 429,714. In total, there were 670,176 cases! The 1,800 judgments handed down in the 12 courts seem little in the face of the backlog of cases. In this article, we intend to present new information that will allow this impressive backlog to be reduced, albeit on a small scale. It tackles, albeit indirectly, the distorted image that the Judiciary is responsible for the delay in tax foreclosures.